ISDC Feedback on CGIAR Portfolio Narrative 2025-2030 - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2024)
The Independent Science for Development Council (ISDC) reviewed the “CGIAR Portfolio Narrative 2025-2030”. ISDC feedback is organized into two sections and an annex and provides a mix of high-level considerations while also providing details and questions for future discussions during Portfolio development.